An Examination of the Clarity of Government Health Websites Using the Centers for Disease Control and Prevention's Clear Communication Index - Gagen, Daniel M.; Kreps, Gary L. (Frontiers in Communication, 2019)
This essay used a content analysis method, the Centers for Disease Control and Prevention research tool, the Clear Communication Index, to evaluate the understandability levels of 10 office and six agency’s health websites, under the U.S. Department of Health and Human Services’ Office of the Assistant Secretary for Health, which are designed for patients to have access to information about health interventions. The objective of this content analysis study was to measure the content of the 10 office websites and six agencies in terms of the clear communication of the health information. The results provide support that these websites do provide relevant health information to consumers and are designed to provide consumers with information support relevant to their health. These findings will help determine best practices for creating website content suitable for all health literacy levels, identify modifications to improve the index and build on previous literature in regard to the importance of using plain language in public health websites.